2023
DOI: 10.1101/2023.07.26.550716
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activation of ATF3 via the Integrated Stress Response Pathway Regulates Innate Immune Response to Restrict Zika Virus

Abstract: Zika virus (ZIKV) is a re-emerging mosquito-borne flavivirus that can have devastating health consequences. The developmental and neurological effects from a ZIKV infection arise in part from the virus triggering cellular stress pathways and perturbing transcriptional programs. To date, the underlying mechanisms of transcriptional control directing viral restriction and virus-host interaction are understudied. Activating Transcription Factor 3 (ATF3) is a stress-induced transcriptional effector that modulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 146 publications
0
8
0
Order By: Relevance
“…Microarray and RNAseq analyses have shown that the levels of ATF5 transcripts increase in cells infected with viruses such as ZIKV or dengue [ 214 ]. ZIKV infection also increases ATF4 transcript and protein levels [ 38 , 39 , 285 ]. In the context of HIV-1 infection, ATF5 transcript levels are up-regulated in Th1Th17 vs. Th1 cells [ 286 ].…”
Section: Atf5 the Paralog Of Atf4mentioning
confidence: 99%
“…Microarray and RNAseq analyses have shown that the levels of ATF5 transcripts increase in cells infected with viruses such as ZIKV or dengue [ 214 ]. ZIKV infection also increases ATF4 transcript and protein levels [ 38 , 39 , 285 ]. In the context of HIV-1 infection, ATF5 transcript levels are up-regulated in Th1Th17 vs. Th1 cells [ 286 ].…”
Section: Atf5 the Paralog Of Atf4mentioning
confidence: 99%
“…In addition to cellular antiviral signaling, autophagy has also been demonstrated to inhibit JEV replication [154]. ATF3 regulates viral infection by stimulating and inhibiting immune responses [20,140,155]. ATF3 has been reported to inhibit cellular antiviral signaling and autophagy by binding to the promoter regions of STAT1, IRF9, ISG15, and ATG5, thereby promoting JEV virus replication [120].…”
Section: Dna Virusmentioning
confidence: 99%
“…Interestingly, compared to its response to JEV infection, ATF3 exhibits a different function in hosts infected with the Zika virus (ZIKV). Research found that ATF3 inhibits ZIKV infection by differentially regulating the transcription of specific innate immune response and autophagy genes [140]. During the infection with ZIKV of A549 cells, ATF3 promotes the transcription of the RIG-I, STAT1, IRF9, and ISG15 genes while simultaneously inhibiting the transcription levels of IFNβ and IFIT2 [140].…”
Section: Dna Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine if the transcriptomic events observed in ZIKV infected cell lines are similar to those in the pediatric patients we infected an A549 cell line with a contemporary ZIKV isolate namely PRVABC59 isolated from Puerto Rico [56] at a high multiplicity of infection and prepared samples for RNA-seq analysis 48 hours post-infection. Although A549 cells are derived from human lung adenocarcinoma, the cell line has an intact immune response and has been used for studies investigating the molecular virology and virus-host interactions of flaviviruses [82]. Moreover, infants with congenital Zika syndrome showed lung disease [83], and high viral titers were reported in the lung of mice infected with ZIKV [68,69].…”
Section: Zikv Infection Of A549 Cultured Cells Shares Transcriptional...mentioning
confidence: 99%